Minimally Invasive Sampling of Surface Coatings for Protein Identification by Peptide Mass Fingerprinting: A Case Study with Photographs. Issue 3 (1st October 2020) - Kirby, Daniel P.; Manick, Annette; Newman, Richard
ABSTRACT: This study investigates the efficacy of a sampling technique to acquire sufficient sample for peptide mass fingerprinting analysis (PMF) with minimal alteration to photograph surfaces. The technique, which is potentially useful for sampling surface coatings in a wide variety of situations, uses very fine polishing film (1–30 μm particles, 14, 000–600 grit) to abrade and remove small amounts of surface material consistent with PMF sample requirements. Several variations of sampling devices were evaluated using coated salt print mock-ups and study collection photographs. This paper discusses those evaluations, proposes an optimized system for sampling thin, proteinaceous coatings for PMF analysis, and cites criteria for deciding whether using the sampling technique is warranted and/or advisable in certain cases.